2011
DOI: 10.1186/1477-5956-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the biofilm proteome of Xylella fastidiosa

Abstract: BackgroundXylella fastidiosa is limited to the xylem of the plant host and the foregut of insect vectors (sharpshooters). The mechanism of pathogenicity of this bacterium differs from other plant pathogens, since it does not present typical genes that confer specific interactions between plant and pathogens (avr and/or hrp). The bacterium is injected directly into the xylem vessels where it adheres and colonizes. The whole process leads to the formation of biofilms, which are considered the main mechanism of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Zinc is a structural and catalytic cofactor in a variety of proteins including Zn-metalloproteases important in digesting plant components for the nutrition of the bacterium [33], [34], [35], [36]. Based on observations that supplemental Zn inhibited biofilm formation in microtiter plates [17] we chose to supplement PD2 media with zinc at 0.25 mM and at 2.5 mM.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc is a structural and catalytic cofactor in a variety of proteins including Zn-metalloproteases important in digesting plant components for the nutrition of the bacterium [33], [34], [35], [36]. Based on observations that supplemental Zn inhibited biofilm formation in microtiter plates [17] we chose to supplement PD2 media with zinc at 0.25 mM and at 2.5 mM.…”
Section: Resultsmentioning
confidence: 99%
“…These include a the non-fimbrial adhesin, YapH [26], the FadL porin [27], citrate synthase [28], UDP-glucose dehydrogenase [19], the molecular chaperone DnaK [29-31], the elongation factor Ef-Tu [29,32], the polynucleotide phosphorylase [33] and a TonB-dependent receptor protein [19] (Table 2). These findings further validate our experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…Ef-Tu was also over-expressed in the wild type strain of Lactobacillus crispatus as compared to an isogenic mutant that lost the aggregative phenotype and strengthening the claim for a role in adhesion [53]. Moreover, in the citrus pathogen Xylella fastidiosa , Ef-Tu was reported to be up-regulated in biofilms [32]. Recent work demonstrated that in X .…”
Section: Resultsmentioning
confidence: 99%
“…A previous studies of the X. fastidiosa proteome revealed differences between the planktonic and biofilm stages in the expression of proteins related to metabolism, motility, attachment, and stress conditions (Silva et al, 2011) and showed the presence of 30 extracellular proteins related to survival and pathogenesis after growth in solid medium for 21 days (Smolka et al, 2003; Silva et al, 2011). In the present study, we identified 48 proteins from strain 9a5c and 44 proteins from strain J1a12, which resulted in the identification of 71 non-redundant proteins, of which 21 were identified in both strains ( Figures 3A,B ).…”
Section: Resultsmentioning
confidence: 95%